Untersuchungen zur Hämostase bei Kindern unter Valproatbehandlung - Schädlich, D.; Friebel, D.; Schallner, J.; Gehrisch, S.; Siegert, G.; Kuhlisch, E.; Knöfler, R. (Hämostaseologie, 2010)
Coagulation parameters were determined in children with valproic acid mono- and valproic acid-lamotrigin combination therapy. Patients, methods: Monotherapy group (n = 22; mean age: 10.5 years) was compared to combination therapy (n = 7; 12.9 years) and a control group (n = 22; 8.7 years). The following parameters were measured: aggregation and ATP-release in whole blood (ADP: 20 μmol/l, collagen: 1 μg/ml, thrombin: 0.5 U/ml), PFA-100® closure times (CT), blood cell counts, global tests, VWF : Ag, VWF : CBA, factors VIII and XIII as well as fibrinogen. Bleeding symptoms were evaluated by using a questionnaire. Results: For ADP- and collageninduced aggregation as well as for ATP release no significant differences between the groups were detected. The combined therapy group showed significantly prolonged CT. Von Willebrand disease was not detected in any of the patients. The platelet count was significantly decreased in the monotherapy group. In six children a mild bleeding tendency was observed, mostly epistaxis. Conclusion: A clinically relevant influence of valproic acid on haemostasis was found only in few cases. However, before surgical procedures an extended coagulation diagnostics is recommended in patients with valproic acid therapy.
Keywords: Valproic acid; haemostasis; children